A Feminist Legacy : the Rhetoric and Pedagogy of Gertrude Buck. (Studies in rhetorics and feminisms., 2009)
The first book-length investigation of a pioneering English professor and theorist at Vassar College, A Feminist Legacy: The Rhetoric and Pedagogy of Gertrude Buck explores Buck's contribution to the fields of education and rhetoric during the Progressive Era. By contextualizing Buck's academic and theoretical work within the rise of women's educational institutions like Vassar College, the social and political movement toward suffrage, and Buck's own egalitarian political and social ideals, Suzanne Bordelon offers a scholarly and well-informed treatment of Buck's achievem.